1981
DOI: 10.1152/ajpendo.1981.240.5.e499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estradiol and progesterone on food intake, body weight, and carcass adiposity in weanling rats

Abstract: Schwartz, Susan M., "Effects of estradiol and progesterone on food intake, body weight, and carcass adiposity in weanling rats." (1981 vi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 67 publications
(104 reference statements)
1
20
0
2
Order By: Relevance
“…In this study, we examined the effect of EB (20 μg/kg) treatment on both food intake and body weight gain in developing rats and demonstrated that estrogen treatment had no effect on food intake in early postnatal days, an observation that is consistent with previous reports [10][11][12]. However, our results indicate that the effect of estrogen treatment appear to become functional around P27 and onwards.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study, we examined the effect of EB (20 μg/kg) treatment on both food intake and body weight gain in developing rats and demonstrated that estrogen treatment had no effect on food intake in early postnatal days, an observation that is consistent with previous reports [10][11][12]. However, our results indicate that the effect of estrogen treatment appear to become functional around P27 and onwards.…”
Section: Discussionsupporting
confidence: 88%
“…All pups were subcutaneously (s.c.) injected daily with 20 μg/kg of estradiol benzoate (EB; Sigma, St. Louis, MO, USA) in 50 μl sesame oil (Nacalai Tesque, Kyoto, Japan) or the vehicle alone at 1200 h for three successive days. This dose of EB is enough to decrease food intake in adult rats [24,25] and has no obvious side effect in P25-55 rats [11]. The vagina did not open in the EB-and vehicletreated rats in any of the present experimental groups.…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…In the present study, subcutaneous administration of progesterone produced significant increase in food intake and thereby body weight in agreement with previous reports. 31 We have observed significantly decreased food intake and body weight in mice treated with Fattolin at dose level of 200 mg/kg and 400 mg/kg. The effect of Fattolin on food intake is mainly due to its active principles which have been reported for various therapeutic effects like hypo lipidaemia, thermo genesis and carminative.…”
Section: 4mentioning
confidence: 69%